How Sustainable Enterprises Can Drive The Sustainable Development - Patrizia Gazzola; Eka Sepashvili; Roberta Pezzetti (European Scientific Journal, ESJ, 2018)
The aim of the paper is to analyze the role of companies as driver of sustainable development and respect for fundamental workers' rights. Trade policies and agreements can have wide-ranging effects on the economy, employment, labour standards, social cohesion, and the environment, including policy development and regulatory aspects. Nowadays the countries are closely tied to one another through trade and investment. This creates a common interest in a well-balanced world economy and properly functioning global system of trade. Thus, the EU wants to ensure that its trade actions are supportive of sustainable development within the EU, in the partner countries, and globally. The sustainability with its economic, social and environmental dimension in all relevant policies is a basic objective set out in the Treaty on the European Union, both as regards the EU's internal policies and external action. Respect for fundamental workers' rights and for environmental protection requirements should be ensured in a context of trade and economic expansion: the jobs created by open trade shall reflect international core labor standards and increased trade flows shall help the rapid spread of green goods, services and technologies around the world. The research presents three case studies on the CSR policy: Nike, Apple and Walmart. These multinationals have been involved in social and environment conflicts. The article researched how companies solved these conflicts and what changes they made in the sustainable policy in relation to those conflicts.